THE IMPORTANCE OF EARLY READING LEARNING IN THE FACE OF 21st CENTURY EDUCATION - Ima Hariyanti Ningsih; Retno Winarni; Roemintoyo Roemintoyo (AL-ASASIYYA: Journal Of Basic Education, 2019)
The increasing technological developments currently have an impact on the world of education, especially in early reading learning. Reading is one of the skills that must be possessed by students, therefore reading skills must be taught at the beginning of entering the educational level. In the 21st century reading skills are included in literacy. It shows that mastery of reading skills is important to be mastered in the face of the 21st century. This research aims to know the importance of reading the beginning to face the 21st century education. The research uses descriptive qualitative methods, with data collection techniques including interviews, observation and documentation. The data validity technique using source trials. Data analysis using data reduction procedures, data presentation, and drawing conclusions. The results of this study can be seen that the beginning of reading learning is emphasized to be mastered by students, considering that in 21st century student must have a skill. Mastered reading skills can help learners to think critically, solve a problem and master the various technologies available.